2020
DOI: 10.1080/20008198.2020.1726071
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged grief disorder in Chinese Shidu parents who have lost their only child

Abstract: Background: China has the largest population of '"loss-of-only-child' parents, that are also known as Shidu parents in Chinese society; however, little is known about their unresolved grief. Objective: This is the first study to examine the grief symptoms, prevalence, comorbidity and potential predictors of prolonged grief disorder (PGD) in such parents, taking into consideration that the new PGD diagnostic criteria ICD-11 will soon be implemented in China. Methods: 149 Shidu parents completed assessments of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 70 publications
0
22
1
Order By: Relevance
“…Prevalence of PGD found in our COVID-19 related bereaved sample (37.8%) is higher than Chinese people bereaved 55 months ago (12.7%) and German-speaking people bereaved 48 months ago (7.3%); both studies used the same measure and diagnostic algorithm [ 39 ]. The number is also higher than the prevalence of PGD in a sample of bereaved Wenchuan earthquake survivors in China (8.47%) [ 16 ] and a group of Chinese Shidu parents (i.e., parents who lost their only child) bereaved 7 years ago (22.2%) [ 47 ], who are undergoing the most painful and traumatic experience than other types of loss and facing physical and psychological challenges [ 48 ]. The number is similar to the prevalence in a large-scale survey of Chinese Shidu parents bereaved 9 years ago (35.5%) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of PGD found in our COVID-19 related bereaved sample (37.8%) is higher than Chinese people bereaved 55 months ago (12.7%) and German-speaking people bereaved 48 months ago (7.3%); both studies used the same measure and diagnostic algorithm [ 39 ]. The number is also higher than the prevalence of PGD in a sample of bereaved Wenchuan earthquake survivors in China (8.47%) [ 16 ] and a group of Chinese Shidu parents (i.e., parents who lost their only child) bereaved 7 years ago (22.2%) [ 47 ], who are undergoing the most painful and traumatic experience than other types of loss and facing physical and psychological challenges [ 48 ]. The number is similar to the prevalence in a large-scale survey of Chinese Shidu parents bereaved 9 years ago (35.5%) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of PGD found in our COVID-19 related bereaved sample (37.8%) is higher than Chinese people bereaved 55 months ago (12.7%) and German-speaking people bereaved 48 months ago (7.3%); both studies used the same measure and diagnostic algorithm [39]. The number is also higher than the prevalence of PGD in a sample of bereaved Wenchuan earthquake survivors in China (8.47%) [16] and a group of Chinese Shidu parents (i.e., parents who lost their only child) bereaved 7 years ago (22.2%) [47], who are undergoing the most painful and traumatic experience than other types of loss and facing physical and psychological challenges [48]. The number is similar to the prevalence in a large-scale survey of Chinese Shidu parents bereaved 9 years ago (35.5%) [49].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported risk factors associated with the development of PGD in Western samples, including gender and age of parent/child and household income (Chiambretto et al, 2010; Pohlkamp et al, 2018). A few studies have explored PGD symptoms among shiduers in China, where researchers found that the number of years since the loss, perception of the family's economic situation, gender, and loss-related memory were prominent risk factors for the development of PGD symptoms (Zhang et al, 2020; Zhang & Jia, 2019). However, it remains unclear about how to help bereaved parents reduce their PGD symptoms and cope with life without their child.…”
Section: Pgd Symptoms After Child Deceasedmentioning
confidence: 99%